208k views
0 votes
Solve.
6 – 7x = 7x – 9x + 11
The value of x is ?

2 Answers

7 votes

Answer: I think it is 2

Step-by-step explanation: 11x - 9x = 2x

User King Chan
by
4.6k points
2 votes

Answer:

Explanation:

Simplifying

6 + -7x = 7x + -9x + 11

Reorder the terms:

6 + -7x = 11 + 7x + -9x

Combine like terms: 7x + -9x = -2x

6 + -7x = 11 + -2x

Solving

6 + -7x = 11 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.

6 + -7x + 2x = 11 + -2x + 2x

Combine like terms: -7x + 2x = -5x

6 + -5x = 11 + -2x + 2x

Combine like terms: -2x + 2x = 0

6 + -5x = 11 + 0

6 + -5x = 11

Add '-6' to each side of the equation.

6 + -6 + -5x = 11 + -6

Combine like terms: 6 + -6 = 0

0 + -5x = 11 + -6

-5x = 11 + -6

Combine like terms: 11 + -6 = 5

-5x = 5

Divide each side by '-5'.

x = -1

Simplifying

x = -1

User MultiGuy
by
4.8k points